2018
DOI: 10.1007/s13365-018-0686-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced facilitation and diminished inhibition characterizes the pronociceptive endogenous pain modulatory balance of persons living with HIV and chronic pain

Abstract: Chronic pain in persons living with HIV (PLWH) may be related to alterations in endogenous pain modulatory processes (e.g., high facilitation and low inhibition of nociception) that promote exaggerated pain responses, known as hyperalgesia, and central nervous system (CNS) sensitization. This observational study examined differences in endogenous pain modulatory processes between 59 PLWH with chronic pain, 51 PLWH without chronic pain, and 50 controls without HIV or chronic pain. Quantitative sensory testing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Experimental protocols for the assessment of endogenous pain modulatory balance included TS of mechanical pain and CPM, each assessed at the lumbar spine. TS & CPM protocols were carried out in accordance with commonly recommended methods [ 19 , 30 , 37 , 38 ]. Our findings suggest that a pro-nociceptive pain modulatory balance, characterized by a high degree of endogenous pain facilitation (i.e., TS of mechanical pain), may be an important contributor to future episodes of movement-evoked cLBP severity and poorer physical function when assessed with the SPPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental protocols for the assessment of endogenous pain modulatory balance included TS of mechanical pain and CPM, each assessed at the lumbar spine. TS & CPM protocols were carried out in accordance with commonly recommended methods [ 19 , 30 , 37 , 38 ]. Our findings suggest that a pro-nociceptive pain modulatory balance, characterized by a high degree of endogenous pain facilitation (i.e., TS of mechanical pain), may be an important contributor to future episodes of movement-evoked cLBP severity and poorer physical function when assessed with the SPPB.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, TS of mechanical pain was examined exclusively as a measure of endogenous pain facilitation. Previous research has demonstrated that TS of mechanical pain is more clinically relevant than TS of thermal pain for predicting musculoskeletal clinical pain severity [ 15 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…As such, a complete methodology can be found elsewhere. 25 All participants provided written informed consent and study procedures were approved by the University of Alabama at Birmingham Institutional Review Board and conducted in compliance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Our QST methodology has been described elsewhere. 25 In short, heat pain threshold (HPTh), heat pain tolerance (HPTo), and temporal summation (TS) of heat pain were assessed prior to TS of mechanical pain. Following TS procedure, conditioned pain modulation (CPM) was assessed.…”
Section: Quantitative Sensory Testing (Qst)mentioning
confidence: 99%
“…In chronic pain cohorts, psychophysical pain assessments, such as quantitative sensory testing (QST) and conditioned pain modulation (CPM), can be used to demonstrate patterns of sensory change hypothesised to be linked to underlying pain mechanisms, with the potential to guide individualised analgesic treatment (Arendt-Nielsen et al, 2017;Baron et al, 2017;Campbell et al, 2012;Demant et al, 2014;Höper et al, 2014;Nahman-Averbuch et al, 2011;Owens et al, 2019;Simpson et al, 2010;Westermann et al, 2012;Yarnitsky et al, 2012). QST is a method of assessing somatosensory function, providing a semi-objective quantification of sensory large and small nerve fibre function (Gracely, 1999;Greenspan, 2001;Haanpaa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%